Effect of Tarantula cubensis alcoholic extract on tumour pathways in azoxymethane-induced colorectal cancer in rats - Akcakavak, Gokhan; Ozdemır, Ozgur (Acta veterinaria Brno, 2023)
The aim of this study was to determine the effects of Tarantula cubensis alcoholic extract (TCAE) on tumour development pathways in azoxymethane (AOM)-induced colorectal cancer in rats by molecular methods. Eighteen paraffin-embedded intestinal tissues, six from each group, were studied in the healthy control (C), cancer control (CC), cancer + TCAE (C-TCAE) groups. Sections of 5 μm thickness were taken from the paraffin blocks and submitted to staining with haematoxylin-eosin. In the histopathological examination, the number of crypts forming aberrant crypt foci (ACF) and the degree of dysplasia in the crypts were scored. Real-time PCR analysis was completed to determine β-catenin, KRAS (Kirsten rat sarcoma virus), APC (adenomatous polyposis coli) and P53 expressions on samples from each paraffin block. The grading scores of the number of crypts forming ACF and dysplasia in the crypts showed an evident decrease in the C-TCAE group in comparison to the CC group (P < 0.05). In real-time PCR analysis, mRNA expression levels of P53 (P > 0.05) and APC (P < 0.001) genes were found to be increased in the C-TCAE group according to the CC group. The expression levels of KRAS (P < 0.01) and β-catenin (P < 0.005) mRNA were found significantly decreased in the C-TCAE group. In conclusion, the effects of TCAE on AOM-induced colorectal cancer (CRC) in rats were evaluated molecularly; TCAE was found to modulate some changes in CRC developmental pathways, inhibiting tumour development and proliferation, and stimulating non-mutagenic tumour suppressor genes. Thus, it can be stated that TCAE is an effective chemopreventive agent.